Going Beyond Merely Providing Expertise and Services - Timothy J. Shaffer (The University of Alabama, 2022)
Review of the book: Beere, C.A., Votruba, J.C., & Wells, G.W. (2011). Becoming an Engaged Campus: A Practical Guide to Institutionalizing Public Engagement. San Francisco, CA: Jossey-Bass. ISBN: 978-0470532263